HOW FEEDBACK AND WASS EFFECTIVENESS INFLUENCE CONTINUANCE INTENTION THROUGH ON TRUST IN THE PLATFORM: MEDIATING EFFECT OF HABIT - Muh. Tri Yoga Deni Saputra; Sholihah , Dewi (Jurnal Mebis, 2023)
The Intention to make a transaction again is something that can build trust from consumers, so it is an important topic to research. This study aims to determine the effect of feedback and WASS Effectiveness through Trust in platforms on continuance intention, which is moderated by the habit of Shopee. This research is explanatory research with a sample of 114 respondents using the purposive sampling technique of 114 respondents who have the habit of accessing the Shopee platform for at least 2 hours. And these respondents understand the importance of WASS in ensuring the security of their personal data. Data were analyzed using the Structural Equation Model (SEM) method. The results of this study prove that feedback and WASS Effectiveness have a significant effect on trust in platforms, as well as trust in platforms which have a significant effect on continuance intention and habit as moderation strengthens the relationship between trust in platforms and continuance intention. The results can be used to advise e-commerce providers to improve responsive and interactive attitudes towards the consumer experience. E-commerce providers can consider strategies and quality improvement efforts received through consumer feedback responses and maintain their WASS. As a theoretical contribution, this study uses the ECM model to explore the determinants of continuance intention in online purchases.